Rehabilitating the injured throwing shoulder: A comprehensive EMG analysis of rotational shoulder exercise - Alizadehkhaiyat, O.; Hawkes, D. H.; Frostick, S. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Effective overhead throwing, a key component of many professional sports, requires a balance between rotational shoulder strength and flexibility. Injuries are common and rehabilitation protocols are central for successful and timely treatment. There is an absence of comprehensive studies with regard to shoulder rotational exercises. Hence this electromyographic study aimed to describe shoulder girdle muscle activation strategies during eight common rotational shoulder exercises. Method: EMG was recorded in 30 healthy subjects from 16 shoulder girdle muscles (surface electrodes: anterior, middle and posterior deltoid, upper, middle and lower trapezius, upper and lower latissimus dorsi, upper and lower pectoralis major; fine wire electrodes: supraspinatus, infraspinatus, subscapularis and rhomboid major) using a telemetric EMG system. Five external rotation (EXT.R.) exercises (0o and 90o of abduction, and with towel, prone external rotation, side lying internal rotation) and three internal rotation (INT.R.) exercises (0o and 90o of abduction, zero-position internal rotation) were included. EMG amplitude was normalised to external or internal rotation MVC as appropriate. Mean EMG amplitudes between exercises were compared using repeated measures ANOVA. Results: EXT.R. Exercises: significantly higher activation of deltoid was seen in EXT.R. at 90o abduction compared to other exercises (73.7% vs 12.4-27.2%; p<0.001). Peri-scapular muscle activation was highest in EXT.R. at 90o abduction and prone EXT.R. (76.7-83.2% vs 28.2-45.5%; p=0.013 - <0.001). Activation of latissimus dorsi and teres major was significantly higher during prone EXT.R. (64.1% vs 18.1-48.4%; p<0.001). Activation of the rotator cuff muscles was similar across all exercises. INT.R. Exercises: the highest deltoid activity was seen during INT.R. at 90o abduction, followed by zero-position internal rotation and lowest during INT.R. at 0o abduction (261.6% vs 190.1% vs 40.9%; p=0.003 - <0.001). A similar activation pattern was seen for peri-scapular muscles. The highest activation of pectoralis major was in zero-position INT.R. (25.4% vs 4.9-15.7%; p=0.002-<0.001). Significantly higher levels of rotator cuff activation were seen during INT.R. at 90o abduction (325.0% vs 94.0-188.3%; p=0.005-0.017). Discussion: This study provides a comprehensive description of muscles activation during common rotational shoulder exercises. It enables sport medicine professionals to target specific shoulder girdle muscles during rehabilitation protocols while minimising the effect of others, forming the basis for exercise prescription. Furthermore, the information can be used for tailored and targeted training of muscles involved in throwing sports.